2020
DOI: 10.1038/s41598-020-74236-0
|View full text |Cite
|
Sign up to set email alerts
|

Active site competition is the mechanism for the inhibition of lipoprotein-associated phospholipase A2 by detergent micelles or lipoproteins and for the efficacy reduction of darapladib

Abstract: Lipoprotein associated phospholipase A2 (Lp-PLA2) has been characterized for its interfacial activation as well as inhibition by detergent micelles and lipoprotein particles. The enzyme has been shown to bind on the surfaces of hydrophobic aggregates, such as detergent micelles, lipoprotein particles and even polystyrene latex nanobeads. Binding to hydrophobic aggregates stimulates the activity of Lp-PLA2 but may not be the necessary step for catalysis. However, at higher concentrations, detergent micelles, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A role in atherothrombosis has also been proposed for Lp‐PLA 2 which is present on rupture‐prone plaques but not on stable plaques. Unfortunately, the Lp‐PLA 2 inhibitor darapladib failed to demonstrate efficacy in two large clinical trials 79 …”
Section: Oxidized Phospholipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A role in atherothrombosis has also been proposed for Lp‐PLA 2 which is present on rupture‐prone plaques but not on stable plaques. Unfortunately, the Lp‐PLA 2 inhibitor darapladib failed to demonstrate efficacy in two large clinical trials 79 …”
Section: Oxidized Phospholipidsmentioning
confidence: 99%
“…Unfortunately, the Lp-PLA 2 inhibitor darapladib failed to demonstrate efficacy in two large clinical trials. 79…”
Section: Oxpls Coagulation and Thrombosismentioning
confidence: 99%
“…It has recently been shown that subcutaneous administration of lysolipids to rats led to a decrease in the activity of sPLA2 in the blood [ 26 ]. In addition, the inhibitory effect of detergent micelles on lipoprotein-associated PLA2 has been shown [ 27 ]. In both cases we assume that micelles formed by lysolipids or detergents are responsible for PLA2 binding and subsequent enzyme take-off from the reaction.…”
Section: Preventing Spla2 Binding To the Target Membranementioning
confidence: 99%
“…Since the majority of serum Lp-PLA2 is bound to LDL particles, the higher affinity of darapladib to HDL may provide an additional explanation for its failure. In case the hypothesis of different activity of HDL or LDL-bound Lp-PLA2 is a true, a more detailed understanding of this phenomenon could also help to clarify darapladib inefficiency [ 534 ].…”
Section: Currently Available Hdl-targeted Therapiesmentioning
confidence: 99%